Session Topic: Corporate Finance and the Capital Asset Pricing Model: Discussion - Hamada, Robert S. (Journal of Finance, 1977)
Robert S. Hamada, Session Topic: Corporate Finance and the Capital Asset Pricing Model: Discussion, The Journal of Finance, Vol. 32, No. 2, Papers and Proceedings of the Thirty-Fifth Annual Meeting of the American Finance Association, Atlantic City, New Jersey, September 16-18, 1976 (May, 1977), pp. 333-336